Dismenore Primer Pada Remaja Putri: Peran Tingkat Stres dan Indeks Massa Tubuh (IMT) - Dwi Uniar; Achirman; Ria Simanungkalit; Exsos Grend Dais (STIKES Bina Usada Bali, 2026)
Background: Primary dysmenorrhea is one of the most common gynecological disorders among adolescent girls during menstruation, caused by increased prostaglandin production that triggers uterine contractions and menstrual pain. Psychological factors, such as stress, may intensify pain perception through hormonal imbalance, while abnormal Body Mass Index (BMI) can disrupt reproductive hormones and menstrual cycles. This study aimed to examine the relationship between stress level, BMI, and the incidence of primary dysmenorrhea among adolescent girls. Methods: This quantitative analytic study employed a cross-sectional design involving 99 adolescent girls selected using a total sampling technique. Data were collected using questionnaires and analyzed through univariate and bivariate analyses with the Chi-square test. Results: Most participants were aged 14–16 years (77.8%). The majority experienced moderate primary dysmenorrhea (51.5%), had severe stress levels (38.4%), and had a normal BMI (51.5%). Bivariate analysis revealed significant associations between stress level and primary dysmenorrhea (p<0.001), as well as between BMI and primary dysmenorrhea (p<0.001). Conclusion: Stress level and BMI were significantly associated with the incidence of primary dysmenorrhea among adolescent girls at MTs Negeri 1 Jakarta. These findings highlight the importance of reproductive health education focusing on stress management and maintaining optimal nutritional status to reduce the risk of primary dysmenorrhea in adolescents